(untitled) (Medico Legal Update, 2020)
The study aimed at assessing the paternal knowledge and attitude towards exclusive breastfeeding using a descriptive research design. The sample size consisted of 125 fathers of children in the age group of ? 6 months to 2 years of age. A Convenient Sampling was used for selecting the fathers. The demographic profile of the fathers and infants was assessed through a structured interview. Paternal Knowledge and Attitude towards exclusive breastfeeding was assessed with the help of a self-administered Questionnaire and a self-administered Opinionnaire. The Study findings revealed that nearly 74% of fathers had good knowledge on exclusive breastfeeding and nearly 69% of fathers had positive attitude towards exclusive breastfeeding. Study also revealed a positive correlation (r=0.32) between paternal knowledge and attitude towards exclusive breastfeeding. A statistically significant association was found between paternal knowledge and paternal age, family type and residence at p<0.05 and a statistical significant correlation was found between paternal attitude and paternal age, employment status, family type, NICU stay of infant and residence at 5% level of significance (p<0.05). The study helped to conclude that fathers are aware about Exclusive breastfeeding and fathers with good knowledge had a positive attitude towards Exclusive breastfeeding. Hence fathers can be a source of great support to their partners and help to promote the culture of Exclusive breastfeeding.